2018
DOI: 10.1002/fuce.201700217
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Study of Water Transport in PEMFCs with Electrosprayed Catalyst Layers

Abstract: Water transport in proton exchange membrane fuel cells (PEMFCs) with electrosprayed catalyst layers is analyzed by means of water collection measurements. With this aim, single cells have been studied with different catalyst layers configuration: electrosprayed layer in cathode (EScat), in anode (ESan), and in both electrodes (ESboth). The electrosprayed catalyst layers show macroporous morphology and superhydrophobicity (water contact angle θ > 150°) . Initial polarization curves, taken after a few hours from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…They suggested that the optimal MEA will be obtained when prepared using the electrosprayed catalyst layer in the cathode and the hydrophilic catalyst layer in the anode. 349 In addition, the mass transport resistance of the electrosprayed and airbrushed catalyst layers were measured to investigate the effect of mass transport in the electrosprayed catalyst layer. The electrosprayed catalyst layer exhibited a smaller mass transport resistance.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that the optimal MEA will be obtained when prepared using the electrosprayed catalyst layer in the cathode and the hydrophilic catalyst layer in the anode. 349 In addition, the mass transport resistance of the electrosprayed and airbrushed catalyst layers were measured to investigate the effect of mass transport in the electrosprayed catalyst layer. The electrosprayed catalyst layer exhibited a smaller mass transport resistance.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
“…346 Due to its macropores and superhydrophobicity, the electrosprayed catalyst layer enhanced the mass transport and cell performance. 346,349 4.1.1.3. Alternative Methods: Electrospinning.…”
Section: Strategies Used To Improve the Performance Of Real-life Fuel...mentioning
confidence: 99%
See 1 more Smart Citation
“…A CIEMAT air-breathing PEM fuel cell (AB-PEMFC) round prototype based on WO2015025070A1 was used for the experiments [11,18]. The anode chamber consists of a circular PEEK plate with lateral gas fittings for fuel inlet and outlet.…”
Section: Fuel Cell Descriptionmentioning
confidence: 99%
“…For continuous passive operation, the flooding and drying-out of cathode and anode must be prevented, that depend on a delicate equilibrium between different operation parameters [13,14]. Incorporating passive water rejection means, like superhydrophobic layers that repeal the liquid water from porous electrodes [15], or a hydrophilic membrane to allow water permeation from the anode [16] help the passive PEMFC operation, where water management is more critical than for a conventional, flow-field based, PEMFC.…”
Section: Introductionmentioning
confidence: 99%